Novel tools integrating metabolic and gene function to study the impact of the environment on coral symbiosis - Pernice, Mathieu; Levy, Oren (Frontiers in Microbiology, 2014)
The symbiotic dinoflagellates (genus Symbiodinium) inhabiting coral endodermal tissues are well known for their role as keystone symbiotic partners, providing corals with enormous amounts of energy acquired via photosynthesis and the absorption of dissolved nutrients. In the past few decades, corals reefs worldwide have been increasingly affected by coral bleaching (i.e., the breakdown of the symbiosis between corals and their dinoflagellate symbionts), which carries important socio-economic implications. Consequently, the number of studies focusing on the molecular and cellular processes underlying this biological phenomenon has grown rapidly, and symbiosis is now widely recognized as a major topic in coral biology. However, obtaining a clear image of the environmental interplay and effects of this mutualistic symbiosis remains challenging. Here, we review the potential of recent technological advances in molecular biology and approaches using stable isotopes to fill critical knowledge gaps regarding coral symbiotic function. Finally, we emphasize that the largest opportunity to achieve the full potential in this field arises from the integration of these technological advances.